LAW509: Halal Related Laws / Faculty of Law - UiTM, Faculty of Law (2023)
This course introduces the students to the fundamental concepts of Halal under the Islamic Law and its transformation into Halal Related Laws under the Malaysian context. The students will be equipped with the knowledge of Halal Related Laws, basic skills of applying the laws to the issues relating to the industry and the society for the purpose of offering acceptable recommendations to the issues.